Application of the Canadian Water Quality Index (CCME-WQI) for Aquatic Life to Assess the Effect of Tharthar Water upon the Quality of the Tigris Water, Northern Baghdad City,Iraq - Majeed, Osama S.; Muhanned R. Nashaat; Al-Azawi , Ahmed Jasim M.; Zaher Drira (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The present study aims to assess the effect of the Tharthar Canal as an outlet canal that feeds back from the Tharthar Lake on the quality of the Tigris water. Utilizing a Canadian Water Quality Index (CCME-WQI) for the protection of aquatic life Water samples were obtained every month from January to December of 2020. Six different sites were selected: four along the Tigris River and two on the Tharthar Canal. Seven ecological parameters were used to assess water quality depending on importance and availability: water temperature, Water Temperature, Turbidity, Dissolved Oxygen (DO), Total Dissolved Solids (TDS), pH, Nitrate (NO3-) and Phosphate ( . The study demonstrated that the water quality of the Tharthr canal ranked as a fair class, whereas that of the main river fluctuated from marginal class before the confluence area to fair class downstream of the confluence. Also, three variables, including water temperature, turbidity, and total dissolved solids, were not meeting water quality standards.